Advanced listening comprehension : developing aural and notetaking skills - Dunkel, Patricia; Pialorsi, Frank (Boston, Mass. : Thomson/Heinle, 2005)
Introduces the fundamentals of listening and note-taking using written exercises and audio activities.
Keywords: English language -- Textbooks for foreign speakers; Listening; Note-taking.